Research on the theoretical basis of innovation clusters and some suggestions for Vietnam - Nguyen Xuan Hoa; Tran Vu Tuan Phan; Nguyen Quoc Hung; Nguyen Quoc Dat; Tran Minh Huyen (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
Innovation strategy in general, and the formation and development of Clusters of Innovation in particular, are not exclusive activities of the state or a single enterprise. ICs serve as a driving force that motivates businesses within the cluster to seek new sources of knowledge and technology, and apply these to products and production processes. Clusters of Innovation are characterized by production networks of independent enterprises, knowledge production factors, bridging institutions, and customers linked to independent enterprises, knowledge production factors, and other bridging institutions and customers in the valuable product chain. In Vietnam, activities related to knowledge transfer, technology, and technology commercialization face numerous challenges due to the absence of a well-defined and developed technology market, as well as limitations in the network of technology transfer organizations. Therefore, the research, formation, and development of Innovation Clusters in Vietnam will enhance the connection between the research sector and the production application sector. It will promote the application of technological innovation, leading to the creation of new industries and business methods in Vietnam. Theoretical research on the Cluster of Innovation will lay the groundwork for policy recommendations for Vietnam Code: 23111601